Wecken property for coincidences of boundary-preserving maps between surfaces - Kelly, M. R.; Silva, L. S.; Vieira, J. P. [UNESP] (Elsevier, 2021)
We study the Wecken property for coincidences in the setting of boundary-preserving maps between surfaces with nonempty boundary. We consider the situation where the domain surface has non-negative Euler characteristic and obtain boundary Wecken results for almost all target surfaces.
Keywords: Boundary-preserving maps; Boundary-Wecken; Coincidence